Sustainable Tourism Development in Sungai Apit District Riau Province: Mangrove Ecotourism Factors - Yoswaty, Dessy (Faculty of Fisheries and Marine, Universitas Riau, 2021)
One of the efforts to overcome the problem of environmental damage in the mangrove forest ecosystem is the management of mangrove ecotourism. The concept of mangrove ecotourism is a responsible trip to mangrove forest areas for mangrove forest conservation efforts and improving community welfare. This study aims to examine sustainable tourism development in Sungai Apit District Riau Province: mangrove ecotourism factors. The method used in this research is a survey method, which was determined at 4 (four) research locations, namely Mengkapan Village (Station I), Sungai Kayu Ara Village (Station II), Kayu Ara Permai Village (Station III) and Tanjung Kuras Village (Station IV). Each research station consists of three sampling points for measuring the quality of coastal waters. It is obtained an overview of environmental factors that support the growth of mangrove forests. Research activities have been carried out in April-November 2020. The results showed that the mangrove forest ecosystem in the Sungai Apit District Suitable (S2) to be developed as a mangrove ecotourism area with an average IKW value of Station I was 75.39%; Station II of 76.71%; Station III is 78.82% and Station IV is 76.32%. The potential and attractiveness of mangrove ecotourism in Sungai Apit District has been developed by the Siak Regency government. The strategy for developing mangrove ecotourism in Sungai Apit District based on SWOT analysis and interviews is to prioritize the W-O strategy which consists of: 1) Increasing the participation of stakeholders in the management of mangrove ecotourism; 2). Promote effective ecotourism promotion, information and market activities; 3) Improve coordination between stakeholders properly and 4) Improve the quality of human resources through training and education activities.